Clinical researchAcute effects of different levels of continuous positive airway pressure on cardiac autonomic modulation in chronic heart failure and chronic obstructive pulmonary disease - Reis, Michel S.; Sampaio, Luciana M.M.; Lacerda, Diego; de Oliveira, Luis V.F.; Pereira, Guilherme B.; Pantoni, Camila B.F.; Thommazo, Luciana Di; Catai, Aparecida M.; Borghi-Silva, Audrey (Archives of Medical Science, 2010)
Introduction : Non-invasive ventilation may improve autonomic modulation and ventilatory parameters in severely disabled patients. The aim of the present study was to evaluate the physiological influence of acute treatment with different levels of continuous positive airway pressure (CPAP) on the autonomic balance of heart and respiratory responses in patients with stable chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). Material and methods : A COPD group (n = 10), CHF group (n = 8) and healthy subjects (n = 10) were evaluated. The participants were randomized to receive three different levels of CPAP on the same day: sham ventilation (Sham), 5 cmH20 (CPAP5) and 10 cmH20 (CPAP10) for 10 min. Respiratory rate, end tidal carbon dioxide (ETCO2), peripheral oxygen saturation (SpO2), heart rate (HR), blood pressure and heart rate variability in the time and frequency domains were measured during spontaneous breathing and under the sham, CPAP5 and CPAP10 conditions. Results : All groups experienced a reduction in ETCO2 values during treatment with CPAP (p < 0.05). CPAP increased SpO2 and HR in the COPD group (p < 0.05). The COPD group also had lower RMSSD values during treatment with different levels of CPAP when compared to the control group (p < 0.05). In the CHF group, CPAP5 and CPAP10 increased the SDNN value (p < 0.05). CPAP10 reduced the SDNN value in the COPD group (p < 0.05). Conclusion : The findings suggest that CPAP may cause improvements in the neural control of heart rate in patients with stable COPD and CHF. For each patient, the “best CPAP level” should be defined as the best respiratory response and autonomic balance.